HUMAN LANGUAGE DISORDER - Anwar Ismail (Jurnal Bilingual, 2021)
This research is related to psycholinguistics, neurolinguistics. It is one of the interdisciplinary studies between linguistics and the human brain. Here, it is more to describe the definition and types of human language disorders (language disorder). Language disorders are disorders that involve the processing of lainguistic information. Language disorder problems experienced can involve grammar (syntax and / or morphology), semantics (meaning), or other aspects of language. These problems may be responsive (involving impaired understanding of language), expressive (involving language production), or a combination of the two. The types of language disorders are as follows (1) disturbance of speech mechanism: interference due to pulmonary factors, disturbance due to laryngeal factors, disturbances due to lingual factors, disturbance due to resonance factors. (2) multifactorial distraction: random speaking, speaking propulsively, mutis speaking (mutism). (3) psychogenic disturbances: spoiled speech, seductive speech, stuttering, talkative talk. (4) aphasia: (1) motor aphasia (cortical motor aphasia, subcortical motor aphasia, transcortical motor aphasia). (2) sensory aphasia.